Exclusion of the scientific expert evidence (low epistemic quality) in the admissibility in criminal proceedings of civil law tradition: Dialogue between two legal cultures - Juan Sebastián Vera Sánchez (Revista Brasileira de Direito Processual Penal)
In this paper we analyze the exclusion criteria of scientific expert evidence of low epistemic reliability from two different legal cultures: common law and civil law. We develop the relationship between both groups of criteria to argue that the Daubert criteria may be applicable in civil law when dealing with clear cases. The freedom of proof, the right to evidence and due process are limitations that prevent a broad application of the exclusion of evidence in these cases.